UPAYA PENINGKATAN AKUNTANSI PENJUALAN MELALUI MOTIVASI KERJA KARYAWAN - Zalkha Soraya; Andi Arifwangsa Adiningrat; Sri Andayaningsih; Rahmansyah Rahmansyah (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to determine efforts to increase sales accounting through employee work motivation. Data in this study, carried out at PT. Megahputra Sejahtera Main Mobil Suzuki Gowa. This study uses a saturated sampling technique. the sample used was 38 people. Data analysis method used is central tendency and analysis statistic descriptive The results of this study indicate that employee motivation is related to sales accounting variables, this means that an employee with good communication tries to be motivated to improve sales accounting by efforts to improve product quality and competitive prices